DIFFICULTIES AND CONTRIBUTING FACTORS FACED BY JUNIOR HIGH SCHOOL STUDENTS IN SOLVING DATA REPRESENTATION PROBLEMS - Rahmawati, Lia; Muhtadi, Dedi; Sukirwan, Sukirwan (Program Studi Magister Pendidikan Matematika, Universitas Siliwangi, 2025)
This study aims to analyze the difficulties experienced by students in solving problems related to data presentation. The research employed a descriptive qualitative method with seventh-grade students at a junior high school in Tasikmalaya City as the subjects. Data were collected through written tests and interviews to explore students’ understanding and identify the causes of their difficulties. The results revealed three main types of difficulties: (1) difficulties in presenting data in the form of diagrams such as bar, line, and pie charts, (2) difficulties in converting data into percentages and degrees, and (3) difficulties in reading and interpreting information from diagrams. These difficulties are caused by a lack of understanding of basic concepts, limited technical skills, and the absence of critical thinking habits in interpreting visual data representations.